Efektivitas Pengelolaan Dana Pada Koperasi Simpan Pinjam (KSP) Satahi Suga-Suga Kabupaten Tapanuli Tengah - Rizka ade Pertiwi Situmeang; Safriadi Pohan; Jeniusman A. Hutagalung (JURNAL EKONOMI BISNIS DAN MANAJEMEN, 2023)
: The Satahi Suga Suga Savings and Loans Cooperative operates in the field of lending and borrowing funds. In other words, managing funds as well as possible is the main focus of the activities of the Satahi Suga Suga Savings and Loans Cooperative, because to assess the effectiveness of managing its funds the Satahi Suga Suga Savings and Loans Cooperative cannot use one financial measure, namely profitability alone, but must also involve evaluating various aspects. The research aims to determine the effectiveness of managing the funds of the Satahi Suga Suga Savings and Loans Cooperative for 2021 based on the Regulation of the Minister of State for Cooperatives and Small and Medium Enterprises of the Republic of Indonesia Number 20/Per/M. KUKM/XI/2008 concerning aspects of capital, aspects of productive asset quality, aspects of liquidity, aspects of independence and growth. The subject of this research is the Satahi Suga Suga Savings and Loans Cooperative where the object of evaluation is the management of KSP Satahi Suga Suga funds. Data analysis techniques in this study used descriptive analysis. In this study data was collected through the documentation method. From the results of the study, the soundness level of cooperatives is included in the "Quite Effective" category with a total score of 56.75 out of a total score of 100. If assessed from guidelines for evaluating the effectiveness of fund management, it has a score of 56.75 which is in the total weighted score of 40-60 with the predicate less effective.